Transport, Associated Handling Procedures and Behaviour of Calves Marketed through Chilean Auction Markets - Bravo, Viviana M. (Animals (Basel), 2020)
SIMPLE SUMMARY: Cattle are transported at least once in their lives, primarily associated with marketing. In Chile one of the main channels for selling animals is auctions. At auction markets, the procedures associated with transport of livestock (loading, unloading and travel) are at least duplicated, affecting their welfare. The aims of this study were to describe the procedures associated with transport and handling of calves (cattle < 9 months old) during marketing through auctions, and to evaluate compliance with Chilean law. A survey of drivers who transport calves from originating farms to markets (OM) and from markets to destination farms (MD) was performed. During loading and unloading, handling by stockpersons, facilities, calf fitness for transport, and behaviour were evaluated using protocols. Most drivers claimed having the training required by law, used bedding material, and provided adequate space for the animals; most OM and MD journeys were less than 2 h. Most calves were assessed as fit for transport. Calves slipped often and some practices associated with poor handling were still observed, mainly during loading. Compliance with the law during transport of calves was adhered to; however, associated handling during unloading and loading is still inadequate, evidencing a need for training. ABSTRACT: In Chile, selling animals through livestock markets is common. At markets, stressful events like loading, unloading and travel are at least duplicated. We described procedures associated with transport of calves at 20 markets and evaluated compliance with Chilean law by performing a survey of drivers who transport calves from origin farms to markets (OM) and from markets to destination (MD). During loading and unloading, we evaluated handling by stockpersons, facilities, fitness for transport, and behavioural indicators of the calves through direct observation using protocols. A total of 80% of drivers claimed having the training required by law. The mean travel time was 1 h 31 min for OM and 1 h 44 min for MD journeys (overall range 5 min–40.5 h). Most drivers used bedding material and provided adequate space availability. A total of 99.2% of the observed calves were assessed as fit to transport; slipping, turning back, vocalizing and balking were frequent behaviours observed during loading and unloading. Prohibited practices like prodding and hitting using driving devices were still observed, mainly during loading. Compliance with the law during transport of calves was adhered to; however, the associated handling within markets was still inadequate, evidencing need for training in order to improve animal welfare.